P 48. Cerebrospinal fluid neurofilaments predict disease aggressiveness in Amyotrophic Lateral Sclerosis: an application of the D50 disease progression model. Issue 8 (August 2021) - Dreger, M.; Steinbach, R.; Gaur, N.; Metzner, K.; Stubendorff, B.; Otto W, W.; Grosskreutz, J.
Abstract : Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disorder. As previous therapeutic trials in ALS have been severely hampered by high inter-individual heterogeneity in clinical phenotype, progression speed and survival, the identification of biomarkers that reliably reflect disease progression represents a priority in current ALS research. Here, we aimed to use the D50 disease progression model to investigate correlations between Cerebrospinal fluid (CSF) Neurofilament light chain (NfL) levels and disease aggressiveness in ALS patients. The D50 model quantifies patients" individual disease trajectories and is calculated based on consecutively assessed ALS functional rating scale scores. The derived value D50 is defined as the time taken in months for a patient to lose 50% of his/her functionality and thus provides a unified measure of a patient"s overall disease aggressiveness. The relative D50 (rD50) reflects the individual disease covered and can be calculated for any timepoint in the disease course. The application of the D50 model enabled us to generate a large-scale pseudo-longitudinal analysis thereby overcoming the persistent difficulties in obtaining longitudinal CSF samples from heterogenous ALS patient cohorts. We analyzed detailed clinical data from a well-defined cohort of 156 patients with ALS. The concentration of NfL in CSF samples was measured at two different laboratories using the same procedure. Based on patients" individual D50 values, we defined subgroups with high (<20), intermediate (20–40) or low (>40) disease aggressiveness. NfL levels were compared between these subgroups via analysis of covariance, using an array of confounding factors: age, gender, clinical phenotype, frontotemporal dementia, rD50-derived disease Phase and analysis laboratory. We found highly significant differences in NfL concentrations between all three D50 subgroups ( p  < 0.001), representing an increase of NfL levels with increasing disease aggressiveness, as revealed in post-hoc analyses. The conducted analysis of covariance showed that this correlation was independent of gender, disease phenotype and Phase; however, age, analyzing laboratory, and dementia significantly influenced NfL concentration. We could show that CSF NfL is independent of patients" individual disease covered (rD50 or derived disease Phase). Our results provided strong evidence for the potential of NfL to reflect disease aggressiveness in ALS and in addition proofed to remain at stable levels throughout the disease course. Implementation of CSF NfL as a potential read-out for future multi-center therapeutic trials in ALS is currently constrained by its demonstrated susceptibility to (pre-)analytical variations. Here we show that the D50 model is a sensitive tool that enables the discovery of correlations between clinical characteristics and CSF analytes and can accordingly recommended for future studies evaluating potential biomarkers.